The Ustilago maydis effector Pep1 suppresses plant immunity by inhibition of host peroxidase activity. - Christoph Hemetsberger; Christian Herrberger; Bernd Zechmann; Morten Hillmer; Gunther Doehlemann (PLoS Pathogens)
The corn smut Ustilago maydis establishes a biotrophic interaction with its host plant maize. This interaction requires efficient suppression of plant immune responses, which is attributed to secreted effector proteins. Previously we identified Pep1 (Protein essential during penetration-1) as a secreted effector with an essential role for U. maydis virulence. pep1 deletion mutants induce strong defense responses leading to an early block in pathogenic development of the fungus. Using cytological and functional assays we show that Pep1 functions as an inhibitor of plant peroxidases. At sites of Δpep1 mutant penetrations, H₂O₂ strongly accumulated in the cell walls, coinciding with a transcriptional induction of the secreted maize peroxidase POX12. Pep1 protein effectively inhibited the peroxidase driven oxidative burst and thereby suppresses the early immune responses of maize. Moreover, Pep1 directly inhibits peroxidases in vitro in a concentration-dependent manner. Using fluorescence complementation assays, we observed a direct interaction of Pep1 and the maize peroxidase POX12 in vivo. Functional relevance of this interaction was demonstrated by partial complementation of the Δpep1 mutant defect by virus induced gene silencing of maize POX12. We conclude that Pep1 acts as a potent suppressor of early plant defenses by inhibition of peroxidase activity. Thus, it represents a novel strategy for establishing a biotrophic interaction.